IMPROVEMENT OF TEACHER CAPABILITY IN SOLOK SELATAN DISTRICT IN DEVELOPING MULTIMEDIA THROUGH TRAINING VIDEO EDITING - Hufri Hufri (Pelita Eksakta, 2019)
Education in South Solok District, still lagging behind in the South Sumatra region, the UN ranking in 2016 is ranked 16th out of 19 existing cities / districts. This happens because the teacher uses video processing software that is recorded, so that many phenomena that cannot be used optimally. This PKM aims to improve the ability of teachers to develop text and video editing. The method used is the stage of interaction and discussion, training, training, training, training and development. Monitoring stages and, end of data analysis and report preparation. The instrument was a test of multimedia and video editing and questionnaires for the implementation of PKM activities. The results of data analysis, obtained by the average from the pretest is 14.42, for the average posttest average is 17.21. Then a paired t test was carried out, obtained a significance value of 0,000 <0,05, thus giving the conclusion that this PKM activity had been able to improve the ability of the Solok district junior school teachers in developing learning videos. Based on the questionnaire given at the end of the training activity, results were obtained that participants were very happy and involved in learning at school